FOREIGN ECONOMIC ACTIVITY OF ENTERPRISES: PROBLEMS OF THEORY AND PRACTICE - HRYTSYNA, Lesia; KHARUN, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Foreign Economic Activity (FEA) of Enterprises is a crucial element of the modern economy, as it ensures the integration of national economies into the global system. However, maintaining competitiveness and sustainability in foreign markets requires enterprises to address a range of theoretical and practical challenges related to the effective implementation of foreign economic operations. An analysis of scholarly sources makes it possible to identify several typological approaches to interpreting the concept of FEA, namely: the organizational-legal, institutional-economic, and functional-complex approaches. The latter is considered the most effective from the standpoint of strategic management. This approach enables the consideration of FEA as a dynamic system of interrelated actions encompassing strategic planning, the development of alternatives, strategy implementation, as well as control and adaptation. The specific nature of FEA planning is conditioned by the need to account for a broad range of external factors. In this context, forming a balanced portfolio of international business partners and adhering to the principles of diversification are critically important for minimizing risks and ensuring the stability of international operations. Modern conditions, particularly the martial law in Ukraine, significantly complicate the conduct of FEA by domestic enterprises due to disrupted logistics chains, limited partner options, and a high level of regulatory uncertainty. For effective adaptation to these circumstances, Ukrainian enterprises must actively implement the concepts of strategic adaptability, particularly through strong leadership, knowledge management, flexible human resource management, and the development of information technologies. Only a comprehensive application of these approaches will allow Ukrainian enterprises not only to withstand crises but also to discover new opportunities for growth in international markets.
Keywords: foreign economic activity; management; strategic planning; adaptation; wartime; globalization; risks; efficiency